Stability and Characteristics of Nitroglycerin Sublingual Tablets Available in the Iraqi Market - Saadallah, Mais Salim; Ali, Zahraa Hussein; Alkotaji, Myasar; Amjad, Maryam (Journal of pharmaceutical innovation, 2025)
Background Nitroglycerin is an anti-anginal drug and a vasodilating agent given sublingually as a life-saving medication for prompt relief of acute angina attacks. Being a highly volatile substance, the choice of packaging and storage conditions are crucial for preserving therapeutic efficacy. Although this fact is generally known among pharmacists, the common practice in Iraq is to dispense nitroglycerin tablets in plastic bags or to reuse the original container to keep only a few tablets. To our knowledge, no studies have been conducted in Iraq to investigate the stability of nitroglycerin under these specific handling and storage practices. Objective This work aims to evaluate the nitroglycerin products available in the Iraqi market and investigate their stability after the opening of the original packaging, taking into consideration the common storage practices. Materials and Methods Three different products of nitroglycerin sublingual tablets entitled (A, B, and K) were included in this study. The evaluation tests included the measurements of dimensions, hardness, friability, weight variation, wetting time, water absorption ratio, and disintegration time. Physical stability tests assessed weight loss, alterations in disintegration time, and tablet surface characteristics (via scanning electron microscopy) under different storage conditions, including full or half-full original containers and plastic bags, stored in either light or dim environments. Results All investigated sublingual tablets demonstrated acceptable friability and weight variation, but were harder than the accepted limits. They possessed long wetting times with low water absorption ratios. Moreover, their disintegration times were far longer than the USP requirements for sublingual tablets. The physical stability tests showed rapid loss of nitroglycerin from the tablets, with more than 10% depletion of the labeled content within one month. Stress conditions further prolonged the disintegration time. Furthermore, scanning electron microscopy revealed pore formation on the tablet surfaces following different storage conditions. Conclusion Nitroglycerin sublingual tablets are unstable after package opening, and the practice of storing them in plastic containers should be avoided. In addition, the number of tablets in the container, which is related to the head-space volume, is crucial to maintain stability.